HYPNOTHERAPY DECREASES STRESS IN ELDERLY HYPERTENSION - Kastubi Kastubi; Minarti Minarti; Noer Saudah (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2017)
Stress stimulates the sympathetic nervous encouraging the heart and cause an increasing blood pressure. Efforts to reduce hypertension pharmacological and non-pharmacological. Non-pharmacological experiment of which is hypnosis. The research objective was to analyze the decrease of stress to elderly hypertensive therapy with hypnotherapy. The research design used experimental pretest - Posttest with Control Group. The population were all the elderly with hypertension in the elderly health care center PacarKeling , and Kemayoran Surabaya with 35 elderlies. Number of sample 15 intervention group, 15 control group. The sampling technique used Simple Random Sampling. Variable intervention was therapeutic applications of hypnosis to elderly hypertensive. The dependent variable was the stress in elderly hypertensive. The statistical test used paired t-test. It showed changes in stress to the control group -7.33, while the experminent group amounted to 14.60. Results can reduce stress in the group treated with hypnotherapy an average decrease of 14.6. Results showed that there were differences in the level of stress control and experiment groups with significant value of p = 0.000 (p <0.05), The effect of hypnotherapy was also shown in the systolic blood pressure change between control and experiment groups showed a mean difference of ranks. In the control group 20.8, while in the experimental group 10.2. Mann Whitney test results obtained by the significant value of p = 0.000 (p <0.05) in mean systolic blood pressure differences between control and experiment groups. Hypnotherapy can reduce stress and blood pressure in the experiment group. Causes of stress on the individual such as physical pain, and the outside factor could be due to family problems, economic. Suggestions that hypnosis can be used as a new experiment method stress problem in the elderly